2022
DOI: 10.3390/bios12100790
|View full text |Cite
|
Sign up to set email alerts
|

Staging of Skin Cancer Based on Hyperspectral Microscopic Imaging and Machine Learning

Abstract: Skin cancer, a common type of cancer, is generally divided into basal cell carcinoma (BCC), squamous cell carcinoma (SCC) and malignant melanoma (MM). The incidence of skin cancer has continued to increase worldwide in recent years. Early detection can greatly reduce its morbidity and mortality. Hyperspectral microscopic imaging (HMI) technology can be used as a powerful tool for skin cancer diagnosis by reflecting the changes in the physical structure and microenvironment of the sample through the differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…For example, Sun collected 880 scenes of multidimensional hyperspectral cholangiocarcinoma images and realized further diagnose based on the features from patch prediction [38]. Liu found that the spectral data of nuclear compartments contribute more to the accurate staging of squamous cell carcinoma compared with peripheral regions [39]. In order to have a clearer understanding of this diagnostic process, we calculated the probability of each pixel being classified as gastric cancer based on the spectral-spatial joint diagnosis results, as shown in Figure 11d.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sun collected 880 scenes of multidimensional hyperspectral cholangiocarcinoma images and realized further diagnose based on the features from patch prediction [38]. Liu found that the spectral data of nuclear compartments contribute more to the accurate staging of squamous cell carcinoma compared with peripheral regions [39]. In order to have a clearer understanding of this diagnostic process, we calculated the probability of each pixel being classified as gastric cancer based on the spectral-spatial joint diagnosis results, as shown in Figure 11d.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity for the differential diagnosis of benign and malignant pigmentary skin lesions were 87.5% and 100%, respectively. Liu et al 10 combined HMI with machine learning methods for staging identification of squamous cell carcinoma (SCC) based on hyperspectral data and obtained the highest staging accuracy of 0.952±0.014, and a KAPPA value of 0.928±0.022.…”
Section: Introductionmentioning
confidence: 99%
“…In several research areas, HSI has shown its great potential to discriminate between several tissue structures by analyzing the tissue–light interactions, measured as specific spectral signatures, allowing tissue perfusion assessment [ 8 , 9 ] and tissue differentiation [ 10 , 11 ]. HSI has been successfully evaluated to detect skin cancer [ 12 , 13 , 14 ], gastric cancer [ 15 ], oral cancer [ 16 ], breast cancer [ 17 ], brain cancer [ 18 , 19 , 20 , 21 , 22 ], head and neck cancer [ 23 ], as well as colorectal cancer [ 24 ] in humans. In these previous works, approaches such as support vector machines (SVMs), random forest (RF), and logistic regression (LR) as well as deep learning networks were used to analyze the hyperspectral (HS) image data.…”
Section: Introductionmentioning
confidence: 99%